Driver's license system for points and traffic violations in Santo Domingo, Ecuador period 2000-2019 - Viña Castillo, Carlos Alberto (2022)
The points-based driver's license system is one of the coercive measures that are gaining greater popularity among states, by granting the possibility of penalizing repeat offenders with a reduction of points and, in extreme scenarios, the definitive withdrawal of the driving license. In this article, an analysis of the infractions committed by drivers who use the roads of the Santo Domingo canton, a town in Ecuador, is carried out, establishing the period 2000-2019 for the analysis; the year 2011 was the point of separation between the offenses committed before and after the implementation of the point-based driver's license system. The findings show that the measure contributed to reducing the generation of traffic violations by 18.85% in the 2011-2019 period compared to the 2000-2010 period. The conclusions obtained provide evidence to design public policies related to land transport management and the development of future research.